(untitled) (Global Journal of Human-Social Science, 2012)
Proverbs in Yoruba culture recognize the natural dichotomy that exists between male and female But while it recognizes their co-existence it as well underlines the fact that the relationship between women and men should be founded on equality It is part of human nature to want to dominate one another When this happens both the oppressed and oppressor invent a proverb to back his or her position And so while the oppressor would event one to justify his or her position the oppressed would also think deeply and invent one that would show that the oppressor is oppressing him or her To invent a proverb one must be intelligent and have vast human experience of sociocultural activity of his or her environment It is not enough to be intelligent it has to be combined with age steeped in wide and vast experience It is this that makes a good proverb stands the test of time